2011
DOI: 10.1063/1.3638181
|View full text |Cite
|
Sign up to set email alerts
|

CO2 adsorption on TiO2(101) anatase: A dispersion-corrected density functional theory study

Abstract: Adsorption, diffusion, and dissociation of CO(2) on the anatase (101) surface were investigated using dispersion-corrected density functional theory. On the oxidized surface several different local minima were identified of which the most stable corresponds to a CO(2) molecule adsorbed at a five-fold coordinated Ti site in a tilted configuration. Surface diffusion is characterized by relatively small activation barriers. Preferential diffusion takes place along Ti rows and involves a cartwheel type of motion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
134
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(159 citation statements)
references
References 57 publications
18
134
1
6
Order By: Relevance
“…Oxygen vacancy is an intrinsic defect in metal oxides, which is the most reactive site on the surface and able to modify the structure of the materials and change the electronic and chemical properties of the surface . The surface oxygen vacancies sites of semiconductors play an important role in CO 2 activation CO 2 molecules prefer to adsorb at oxygen vacancy sites with one oxygen atoms of the CO 2 located at bridging oxygen vacancy defects . The attraction between an oxygen vacancy and a CO 2 molecule may lower the reactive barrier due to the generation of an unexpected affinity interaction.…”
Section: State‐of‐the‐art Accomplishments Of Design and Engineering Omentioning
confidence: 99%
“…Oxygen vacancy is an intrinsic defect in metal oxides, which is the most reactive site on the surface and able to modify the structure of the materials and change the electronic and chemical properties of the surface . The surface oxygen vacancies sites of semiconductors play an important role in CO 2 activation CO 2 molecules prefer to adsorb at oxygen vacancy sites with one oxygen atoms of the CO 2 located at bridging oxygen vacancy defects . The attraction between an oxygen vacancy and a CO 2 molecule may lower the reactive barrier due to the generation of an unexpected affinity interaction.…”
Section: State‐of‐the‐art Accomplishments Of Design and Engineering Omentioning
confidence: 99%
“…As a result of the structural transformation, the lowest unoccupied molecular orbital (LUMO) level of the metal oxide decreases lowering its activation energy [39]. However, density functional theory (DFT) calculations performed by Sorescu et al [43] demonstrated that CO2 preferentially binds to the metal oxide surface in a linear geometry. This is most probably due to the low binding energy (−46 kJ/mol) associated with the linear configuration, the considerable energy required to bend CO2 (38.6 kcal/mol) and the significant deformation the metal oxide surface undergoes when binding to bent CO2 [42,43].…”
Section: Photocatalytic Conversion Of Co 2 : Thermodynamics and Kineticsmentioning
confidence: 99%
“…Additionally, several theoretical studies have demonstrated that subsurface oxygen vacancy or interstitial defects enhance the bonding of CO 2 adsorption on reduced TiO 2 anatase surfaces . Yang et al illustrated that CO 2 adsorption on reduced anatase TiO 2 was attributable to an electrostatic competition between attractive (Ti−O) and repulsive (Ti−C) interactions according to their density functional theory calculations .…”
Section: Introductionmentioning
confidence: 99%